PEMBELAJARAN MEMBACA PUISI PADA SISWA KELAS V SD DENGAN METODE CLASSWIDE PEER TUTORING - Rosita, Imas (COLLASE (Creative of Learning Students Elementary Education), 2021)
This research was written because of the low poetry reading skills of the fifth grade students of SDN 041 Cibuntu Warung Muncang. The purpose of this research is to improve the learning achievement of fifth grade elementary school students towards learning Indonesian, especially reading poetry through the Class Wide Peer Tutoring (CWPT) method. In addition, the study also aims to improve teacher performance in applying appropriate learning methods. After implementing the CWPT method, there were 87.6% who could reach the KKM of 30 students. Based on the data on student learning outcomes, it was found that with increased self-confidence, their learning outcomes would also increase. This self-confidence was obtained after the implementation of the CWPT development method which used peer tutors to improve their ability to read poetry. The results of this study are expected to have a positive impact on improving teacher performance and student learning outcomes.Â